(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To build and validate an educational leaflet for the treatment of patients with ulcer of venous etiology. Methods: Methodological study, developed in two stages: construction of the educational leaflet by literature review and content validation of the material by judges specializing in the subject. Results: The instrument obtained a Content Validity Index (CVI) above 0.80; only one item was modified after the judges’ suggestion. Conclusion: The educational leaflet was presented to be understandable and comprehensive for the content.